Valuation for M&A - analysis of a private digital transformation company - Bohne, Michel (2022)
This paper evaluates the theoretical and practical aspects of a private company valuation for a mergers and acquisitions scenario. Based on the case study of Cloud flight, a valuation range was assessed via intrinsic and relative approaches to estimate an appropriate purchase price. In addition, this paper examines potential synergies with a strategic investor. The key findings are: (1) Private companies provide lower comparability due to restricted data disclosure.(2) Corporate valuations are highly sensitive to key input variables, and underlying assumptions are subject to uncertainty. (3) Mergers and acquisitions can accelerate inorganic growth beyond transactions due to arising synergies.